2022
DOI: 10.18041/2322-634x/rcso.1.2022.7887
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias educativas para disminuir los índices de accidentalidad en el tráfico laboral en Colombia.

Abstract: Objetivo: Determinar la importancia que se tiene sobre la educación vial en búsqueda de reducir las lesiones, colisiones y a su vez las muertes producidas en accidentes de tránsito. Métodos: Diseño de tipo teórico descriptivo documental, en la cual se conjugaron la revisión bibliográfica de 16 artículos científicos, y posteriormente se incluyó revisiones de literatura publicadas donde se evidencio y evaluó las intervenciones de seguridad vial. Resultados: Medidas optadas como la Normatividad de Seguridad vial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On many occasions, the conditions and characteristics of the road infrastructure have been considered irrelevant to TA; however, it has been found that road conditions are actually significant on the occurrence of accidents, material losses and fatalities [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…On many occasions, the conditions and characteristics of the road infrastructure have been considered irrelevant to TA; however, it has been found that road conditions are actually significant on the occurrence of accidents, material losses and fatalities [16,17].…”
Section: Introductionmentioning
confidence: 99%